Java ji shu shou ce yuan shu di 7 ban = Java in a nutshell: a desktop quick reference, seventh edition / = Java in a nutshell : a desktop quick reference, seventh edition - Evans, Benjamin J.; Flanagan, David (Ji xie gong ye chu bam she, 2021)
Detailed summary in vernacular field,
Keywords: Java (Computer program language); Web servers; Object-oriented programming (Computer science); Java (Langage de programmation); Serveurs Web; Programmation orientée objet (Informatique)